On the lineage of Aspergillus fumigatus isolates in common laboratory use. (17th September 2020) - Bertuzzi, Margherita; van Rhijn, Norman; Krappmann, Sven; Bowyer, Paul; Bromley, Michael J; Bignell, Elaine M
Abstract: The origin of isolates routinely used by the community of Aspergillus fumigatus researchers is periodically a matter of intense discussion at our centre, as the construction of recombinant isolates have sometimes followed convoluted routes, the documentation describing their lineages is fragmented, and the nomenclature is confusing. As an aide memoir, not least for our own benefit, we submit the following account and tabulated list of strains (Table 1) in an effort to collate all of the relevant information in a single, easily accessible document. To maximise the accuracy of this record we have consulted widely amongst the community of Medical Mycologists using these strains. All the strains described are currently available from one of these organisations, namely the Fungal Genetics Stock Centre (FGSC), FungiDB, Ensembl Fungi and The National Collection of Pathogenic Fungi (NCPF) at Public Health England. Display items from this manuscript are also featured on FungiDB. Lay abstract: We present a concise overview on the definition, origin and unique genetic makeup of the Aspergillus fumigatus isolates routinely in use by the fungal research community, to aid researchers to describe past and new strains and the experimental differences observed more accurately.